PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN INDUSTRI FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013 – 2015 - Yancik Syafitri; Stephanie Angelia Tamba (JURNAL KOMPETITIF, 2017)
This research is intended to know the influence of Debt Equity Ratio (DER), Return on Equity (ROE), Return on Asset (ROA), Earning Per Share (EPS) and Price Earning Ratio (PER) to stock price in 10 pharmaceutical industry Which are listed on the Indonesia Stock Exchange either simultaneously or partially.The result of the research yields the equation Y = 2950 + 0.275 DER + 0.167 ROE + 0.169 ROA + 0.588 EPS + 0.206 PER + e ,showing the positive and significant influence of DER, ROE, ROA, EPS and PER simultaneously to stock price in 10 pharmaceutical industry Which is listed on the Indonesia Stock Exchange in 2013 - 2015. In addition, there are positive and significant influences of DER, ROE, ROA, EPS and PER partially to stock prices on 10 pharmaceutical industry companies listed on Indonesia Stock Exchange in 2013-2015.Keywords: Debt Equity Ratio (DER), Return on Equity (ROE), Return on Assets (ROA), Earning Per Share (EPS), Price Earning Ratio (PER)